2022
DOI: 10.3389/fphys.2022.959009
|View full text |Cite
|
Sign up to set email alerts
|

Short total sleep duration and poor sleep quality might be associated with asthenozoospermia risk: A case-control study

Abstract: Sleep has been related to a variety of health outcomes. However, no association between sleep and asthenozoospermia has been reported. The aim of this study is to first investigate the relationship between sleep status and asthenozoospermia risk. A case-control study, including 540 asthenozoospermia cases and 579 controls, was performed from June 2020 to December 2020 in the infertility clinic from Shengjing Hospital of China Medical University. Data on sleep status were collected by Pittsburgh sleep quality i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Based on previous literatures, we considered age, sex, marital status, multimorbidity, anxiety symptoms and depression symptoms as potential confounders. But education level, tea drinking, and napping duration were significant ( p < 0.05) in comparisons of intergroup differences, which meant these three variables might be related to SCC, and previous studies indicated that they also be linked with sleep 33–36 . Thus, eventually, we included age, sex, residence, education level, marital status, smoking, tea drinking, multimorbidity, napping duration, anxiety symptoms, and depression symptoms in our final model.…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…Based on previous literatures, we considered age, sex, marital status, multimorbidity, anxiety symptoms and depression symptoms as potential confounders. But education level, tea drinking, and napping duration were significant ( p < 0.05) in comparisons of intergroup differences, which meant these three variables might be related to SCC, and previous studies indicated that they also be linked with sleep 33–36 . Thus, eventually, we included age, sex, residence, education level, marital status, smoking, tea drinking, multimorbidity, napping duration, anxiety symptoms, and depression symptoms in our final model.…”
Section: Methodsmentioning
confidence: 93%
“…T A B L E 1iables might be related to SCC, and previous studies indicated that they also be linked with sleep [33][34][35][36]. Thus, eventually, we included age, sex, residence, education level, marital status, smoking, tea drinking, multimorbidity, napping duration, anxiety symptoms, and depression symptoms in our final model.…”
mentioning
confidence: 99%
“…Our research center is located in a mega city of China with high talent competition and socioeconomic burden, and one notable feature that sets it apart from other cities is the high level of work pressure, which, in turn, leads to reduced sleep time, high psychosocial stress, and irregular eating. Studies reported that short sleep durations, late bedtime, and poor sleep quality were associated with impaired sperm health ( 70 , 71 ). Psychosocial stress was also negatively associated with sperm concentration, total count, and motility ( 72 74 ).…”
Section: Discussionmentioning
confidence: 99%
“…External quality control was conducted by experienced technicians through a national quality control program on semen analysis, which was organized by the Society of Reproductive Medicine, Chinese Medical Association ( Li et al , 2022 ). The test items included SC, TSC, total motility, and sperm morphology.…”
Section: Methodsmentioning
confidence: 99%